Incidence and risk factors of myocarditis in hospitalized patients with COVID-19 - Keller, Karsten; Sagoschen, Ingo; Konstantinides, Stavros; Gori, Tommaso; Münzel, Thomas; Hobohm, Lukas (Journal of medical virology, 2023)
Myocarditis as cardiac involvement in coronavirus disease 2019 (COVID-19)-infection is well known. Real-world data about incidence in hospitalized COVID-19-patients and risk factors for myocarditis in COVID-19-patients are sparse. We used the German nationwide inpatient sample to analyze all hospitalized patients with confirmed COVID-19-diagnosis in Germany in 2020 and stratified them for myocarditis. Overall, 176 137 hospitalizations (52.3% males, 53.6% aged ≥70 years) with confirmed COVID-19-infection were coded in Germany in 2020 and among them, 226 (0.01%) had myocarditis (incidence: 1.28 per 1000 hospitalization-cases). Absolute numbers of myocarditis increased, while relative numbers decreased with age. COVID-19-patients with myocarditis were younger (64.0 [IQR: 43.0/78.0] vs. 71.0 [56.0/82.0], p < 0.001). In-hospital case-fatality was 1.3-fold higher in COVID-19-patients with than without myocarditis (24.3% vs. 18.9%, p = 0.012). Myocarditis was independently associated with increased case-fatality (OR: 1.89 [95% CI: 1.33−2.67], p < 0.001). Independent risk factors for myocarditis were age <70 years (OR: 2.36 [95% CI: 1.72−3.24], p < 0.001), male sex (1.68 [95% CI: 1.28−2.23], p < 0.001), pneumonia (OR: 1.77 [95% CI: 1.30−2.42], p < 0.001), and multisystemic inflammatory COVID-19-infection (OR: 10.73 [95% CI: 5.39−21.39], p < 0.001). The incidence of myocarditis in hospitalized COVID-19-patients in Germany was 1.28 cases per 1000 hospitalizations in 2020. Risk factors for myocarditis in COVID-19 were young age, male sex, pneumonia, and multisystemic inflammatory COVID-19-infection. Myocarditis was independently associated with increased case-fatality.